Inventory of Non-Timber Species in Ayer Hitam Utara Forest Reserve, Johor - Bt Muhamad Jais, Nur Najiha; Linatoc, Alona C.; Bin Muhamad Sa’ed, Mohammad Ifratshim; Mohamad, Salasiah (Journal of Sustainable Natural Resources, 2023)
Ayer Hitam Utara Forest Reserve (AHUFR) is one of the permanent reserved forests (PRFs) in Johor, which is consisted of lowland and peat swamp ecosystems. In AHUFR, there has been little progress in the study of non-timber species. Non-timber forest products (NTFPs) are forest products other than timber that are obtained from both plants and animals and are vital to all species, including people. Among the objectives of this research project were the creation of a checklist of non-timber species in the AHUFR, the identification of non-timber species in the forest reserve, and the measurement of the diversity of non-timber species in the forest reserve. Survey was conducted in 10m × 5m quadrats, in which three quadrats were established in two different ecosystems, namely site A (lowland forest) and site B (peat swamp). The preliminary study documented 92 individuals from 19 families and 33 species of non-timber plants. Melastomataceae was the most dominant family, whilst Clidemia hirta (L.) D.Don was the most dominant species. Based on the Shannon-Wiener and Margalef indices, lowland forest indicated higher diversity of non-timber species compared to peat swamp forest.